2023
DOI: 10.1002/aenm.202203506
|View full text |Cite
|
Sign up to set email alerts
|

Superscalar Phase Boundaries Derived Multiple Active Sites in SnO2/Cu6Sn5/CuO for Tandem Electroreduction of CO2 to Formic Acid

Abstract: The electrocatalytic CO2 reduction reaction (CO2RR) to fuels driven by electrocatalysts is a viable strategy for efficient utilization of emitted CO2. CO2RR involves multiple‐steps, including adsorption, activation, hydrogenation, etc. At present, copper‐tin alloy catalysts have shown the capability to reduce CO2 to formic acid or formate. However, their poor adsorption and activation capacities for CO2 molecules, as well as the sluggish kinetics in *H supply restrict the proton‐coupled electron transfer proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 75 publications
1
20
0
1
Order By: Relevance
“…In this work, as a case study of regulated tandem site catalysts, Ni was successfully introduced into the Cu foil by a facile and fast laser irradiation method, which is conducive to the formation of alloys due to the characteristics of rapid heating and cooling during the preparation. 19,20 The obtained CuNi alloy nanoparticles on the Cu foil (CuNi NPs/CF) show the ampere-level NIRR performance with the highest NH 3 production rate of 94.57 mg h −1 cm −2 , the maximum faradaic efficiency (FE) of 97.03% and good stability for 12 h in an ultrahigh-concentration NO 3 − (44.3 g L −1 ) alkaline solution. The introduced Ni sites display great ability of O–H activation and strong capacity of H* supply, which is beneficial for the subsequent hydrogenation steps of NH 3 synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, as a case study of regulated tandem site catalysts, Ni was successfully introduced into the Cu foil by a facile and fast laser irradiation method, which is conducive to the formation of alloys due to the characteristics of rapid heating and cooling during the preparation. 19,20 The obtained CuNi alloy nanoparticles on the Cu foil (CuNi NPs/CF) show the ampere-level NIRR performance with the highest NH 3 production rate of 94.57 mg h −1 cm −2 , the maximum faradaic efficiency (FE) of 97.03% and good stability for 12 h in an ultrahigh-concentration NO 3 − (44.3 g L −1 ) alkaline solution. The introduced Ni sites display great ability of O–H activation and strong capacity of H* supply, which is beneficial for the subsequent hydrogenation steps of NH 3 synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the Co/Sn@C composite maintained a porous frame structure (Figure a), accompanied by crystals such as rhomboids, irregular cuboids, and hexagons, with sizes around 30–40 nm (Figure b). A high-resolution transmission electron microscopy (HRTEM) image of Co/Sn@C (Figure c) shows three distinct lattice spacings of 0.33, 0.27, and 0.16 nm, which are assigned to the (110) crystal plane of tetragonal SnO 2 , , the (002) crystal plane of tetragonal CoSn 2 , and the (002) crystal plane of tetragonal Sn, respectively. Further patterns of selected area electron diffraction (SAED) confirmed the above results.…”
Section: Resultsmentioning
confidence: 99%
“…This tandem catalysis on Cu 6 Sn 5 /oxides provides an abundant supply of hydrogen species (*H) via proton transfer, resulting in enhanced CO 2 RR activity and selectivity. 141 2.4.1.2 Inhibition of the HER and improvement of CO selectivity by Sn doping. Sarfraz et al used Sn, an economical and abundant metal, in combination with oxide-derived copper (OD-Cu) to prepare highly selective catalysts.…”
Section: Co 2 Reduction Reactionmentioning
confidence: 99%
“…This tandem catalysis on Cu 6 Sn 5 /oxides provides an abundant supply of hydrogen species (*H) via proton transfer, resulting in enhanced CO 2 RR activity and selectivity. 141…”
Section: Tin In Representative Electrochemical Reactionsmentioning
confidence: 99%